Strategies for Overcoming University Researchers’ Writer’s Block - V. M. Evdash; N. N. Zhuravleva (Высшее образование в России)
This paper reveals the importance of overcoming writer’s block for university researchers as second language writers. The idea and materials for the paper come from the experience of the Center for Academic Writing “Impulse” at the University of Tyumen, Russia. The target audience of the Center is the university faculty and researchers who have a lack of time to immerse in the writing process, rather they mainly want to obtain an immediate tangible result. However, our research shows that they often get frustrated by their inability to complete their writing piece because they get stuck at different stages of the writing process. For example, some people find it difficult to finish their papers, or others fade away in the middle, but the main problem is to start writing. Thus, they face writer’s block which can be referred to moderate blockage. To overcome the block, we offer the researchers a variety of activities during courses and special projects. This paper describes two strategies: classroom intervention including mainly pre-writing activities, such as freewriting, looping, word association, aimed to overcome the fear of a white page, and individualized intervention based on the project entitled “Drop in & Reboot your Writing”. The project comprised 10-20 weekly individual meetings lasting for 30 minutes and aiming at dealing with a particular writing issue. The individual approach to each participant led to a better understanding of the causes of writer’s block and finding the cures. These strategies aim to develop researchers’ positive attitude to writing, to enable them to boost their awareness of the writing process in receiving the desired results, and build confidence as second language writers.